Urinary Tumor Markers for Detection and Surveillance in Non-Muscle Invasive Bladder Cancer - Mohamed Jamal Saadh1, Abeer Mohammad Kharshid1, Hala Mousa Sbaih1, Khalil Altaif1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: Cystoscopy still remains the gold standard for diagnosis and follow-up monitoring of bladder cancer (BC). Unfortunately, it is an invasive, and the urine cytology is a highly specific, sensitivity for detection of low grade tumors is only 4% to 31%. The advent of noninvasive urine-based markers as well as other novel modalities has yielded improved diagnostic accuracy. Material and method: Pubmed/Medline search was conducted to identify original articles, review articles, and editorials regarding urine-based biomarkers for screening, early detection, and surveillance of urothelial carcinoma of the bladder. Results: urinary marker shave shown higher sensitivity compared with cytology, and most markers suffer from lower specificity than cytology. In this review, we aimed to summarize the current knowledge on commercially available and promising investigational Urinary tumor markers for detection and surveillance in Non-Muscle Invasive BC. Conclusions: biomarkers into clinical decision making will be of value for BC detection and screening in the future.